A Textual Meaning Analysis of Drama Script “Diversity” Performed by the Seventh Class Students of the University of PGRI Semarang in English Drama Performance in 2016 - Rina Martiana Fitri; Arso Setyaji; Rahmawati Sukmaningrum (Universitas PGRI Semarang, 2017)
The objectives of the research are: 1) to identify textual meaning realized in the dialogue of drama script “Diversity”. 2) to know the dominant theme realized and the reason of dominant theme realized in the dialogue of drama script “Diversity”. 3) to know the contribution of drama script on textual meaning analysis in English Language Teaching. This research is categorized as qualitative descriptive. The instrument of this research was using textual meaning analysis of drama script “Diversity” that was performed on January 6th, 2016 by the seventh students semester in English drama performance. To collect the data, the researcher found the clauses and identified the data. The clauses consist of 194 clauses. According to textual meaning analysis, the researcher found 92 clauses of topical theme, 50 clauses of interpersonal theme, 52 clauses and 50 clauses of textual theme. So, the topical theme is the dominant theme with 47,4% from all themes. This research can give a contribution to the English language teaching in learning systemic functional grammar especially in textual meaning analysis. The lecturer can use this media that is drama script as a media to explain the material about textual meaning analysis. Through this way, the students can learn easily without reading a thick book. On the basis of conclusion, several suggestions can be offered. The lecturer may use that drama script in learning systemic functional grammar especially in textual meaning analysis. The learners may use this drama script as other alternative reference in learning systemic functional grammar especially in textual meaning analysis to improve their analysis in modern grammar ability.